Sistema de gestión de inventarios en la empresa “Bycace” ubicada en el cantón Latacunga, provincia de Cotopaxi en el periodo enero – diciembre 2014 - Chasi Guanoluisa, Erika Jacqueline (2015)
The research was included practical and reliable information Company Byron Cardenas Cerda "BYCACE" difficulties and inconveniences was detected in the management and control of merchandise, in order to implement the system of inventory management that contributed to the improvement in buying and selling it. The research collected sufficient appropriate descriptive information and analysis tools and observation techniques such as: surveys and interviews was used by collecting and analyzing data to meet the objective. The execution of the inquiry showed positive results as a manual of procedures and functions ending with an analysis of FENIX accounting program, which contributed to the improvement in the processes of buying and selling stocks, which led from receipt was drawn up the release to the final consumer, allowing greater control of goods which facilitated the smooth running of business operations and reduced the drawbacks in marketing, taking appropriate decisions as opposed to continuous improvement.